Mechanism of Action of Ulipristal Acetate for Emergency Contraception: A Systematic Review - Rosato, Elena; Farris, Manuela; Bastianelli, Carlo (Frontiers in Pharmacology, 2016)
SUMMARY Ulipristal acetate (UPA) is now recommended as first choice hormonal Emergency Contraception (EC), due to its higher efficacy and similar safety compared to Levonogestrel - EC. Even though all trials demonstrated that the first mechanism of action is inhibition of ovulation, some authors still postulate that a post fertilization effect is also possible, raising the alert on medication and fostering the ethical debate. A Medline database search was performed in order to find recent articles related to UPA’s effects on ovulation, on fallopian tube and on endometrium. We also analyzed the effects on sperm function and pregnancy. All studies conclude that UPA is effective in inhibition of ovulation even when administered shortly before LH peak. The effects on fallopian tube are unclear: according to some authors UPA inhibits ciliar beat through an agonistic effect on progesterone receptors, according to others it antagonizes the progesterone-induced ciliar beat decrease. Concerning the action on endometrium and on embryo implantation most of the studies concluded that low dose UPA used for EC has no significant effect on the decrease of endometrial thickness and on embryo’s attachment, but these results are still matter of debate. Finally recent evidence suggests that UPA modulates human sperm functions while it has no effect on established pregnancy. To date the majority of the evidence concur in excluding a post-fertilization effect of UPA, even though more studies are needed to clarify its mechanism of action.